2006
DOI: 10.1002/jbm.a.30605
|View full text |Cite
|
Sign up to set email alerts
|

Effect of molecular weight on the transfection efficiency of novel polyurethane as a biodegradable gene vector

Abstract: New polyurethane 2-diethylaminoethylamine-polyurethane (LGEA-PU) containing poly(ethylene glycol) segments and tertiary amines was synthesized. LGEA-PU self-assembled readily with the plasmid DNA (pCMV-betagal) in HEPES buffer and was characterized by dynamic light scattering, zeta potential, atomic force microscopy, and XTT cell viability assays. To examine the effect of molecular weight of LGEA-PU systems on transfection, LGEA-PU systems of four different molecular weights (LGEA-PU99, LGEA-PU59, LGEA-PU24, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(10 citation statements)
references
References 25 publications
1
9
0
Order By: Relevance
“…Figure 5 shows the relative cell viability of Neuro 2 A cells, 24 h after transfection with the polyplexes prepared at different N/P ratios. Cytotoxicity positively correlated with polymer molecular weight, in good agreement with earlier findings on PEI, PLL and other polymers (8,12,19,31,32). Polyplexes based on the starting polymer showed significant cytotoxicity, similar to polyplexes based on the high molecular weight polymer fractions (ppz950 and ppz570).…”
Section: Resultssupporting
confidence: 91%
“…Figure 5 shows the relative cell viability of Neuro 2 A cells, 24 h after transfection with the polyplexes prepared at different N/P ratios. Cytotoxicity positively correlated with polymer molecular weight, in good agreement with earlier findings on PEI, PLL and other polymers (8,12,19,31,32). Polyplexes based on the starting polymer showed significant cytotoxicity, similar to polyplexes based on the high molecular weight polymer fractions (ppz950 and ppz570).…”
Section: Resultssupporting
confidence: 91%
“…For example, Shau and coworkers synthesized 2-diethylaminoethylaminepolyurethane (LGEA-PU), consisting of PEG segments and tertiary amines, via step polymerization and post-chemical modification. 125 LGEA-PUs were capable of complexing DNA to form LGEA-PU59/DNA complexes that efficiently transfected COS-7 cells. It was also found that the molecular weight of LGEA-PUs had a significant effect on transfection ability.…”
Section: Polyurethanesmentioning
confidence: 99%
“…Since the zeta potential of studied complexes is similar (from +16 to +20mV, except the dextran) and only non-specific interaction to the studied cells is discussed, the effect of cell surface charge with the counter-charge complexes is minimal. In a series of polycationic polymers (based on the same framework in structure), the higher molecular weight of a polymer has, the better transfection efficiency would be (40). Results show that the lowest Mw (19 kDa) PDAMA bears the worst transfection but the PEI in a similar Mw (25 kDa) showed the best transfection activities.…”
Section: Correlation Between the Alterations Of Dna Spectra In The Pr...mentioning
confidence: 99%